Statistics for Applied Behavior Analysis Practitioners and Researchers - Cox, David J; Vladescu, Jason C (Critical Specialties in Treating Autism and Other Behavioral Challenges, 2023)
Statistics for Applied Behavior Analysis Practitioners and Researchers provides practical and useful content for individuals who work directly with, or supervise those who work directly with, individuals with ASD. This book introduces core concepts and principles of modern statistical analysis that practitioners will need to deliver ABA services. The organization of the book works through the flow of behavior analytic service provision, aiming to help practitioners read through research, evaluate intervention options, incorporate statistics in their analysis of time-series intervention and assessment data, and effectively communicate assessment and intervention effects using statistics. As professionals who provide applied behavior analysis (ABA) services are required to use evidence-based practices and make data-based decisions regarding assessments and interventions, this book will help them take a modern, scientific approach to derive knowledge and make decisions based on statistical literacy.